2010
DOI: 10.1519/jsc.0b013e3181e2e19b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Exercise Order on Maximum Strength and Muscle Volume in Nonlinear Periodized Resistance Training

Abstract: The purpose of this study was to examine the influence of exercise order on strength and muscle volume (MV) after 12 weeks of nonlinear periodized resistance training. The participants were randomly assigned into 3 groups. One group began performing large muscle group exercises and progressed to small muscle group exercises (LG-SM), whereas another group started with small muscle group exercises and advanced to large muscle group exercises (SM-LG). The exercise order for LG-SM was bench press (BP), machine lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 7 publications
1
38
0
11
Order By: Relevance
“…This exercise--order recommendation has been supported by studies that found greater strength gains (Dias et al 2010;Simão et al 2010;Spineti et al 2010) and hypertrophy Spineti et al 2010) in muscles that were trained at the beginning, rather than at the end, of a session during a long--term training program. Furthermore, studies examining the effect of exercise order (i.e., either large or small muscle--group exercises performed first in a training session) on repetition performance demonstrated significantly greater total repetitions (across all sets) for the same exercise when large muscle--group exercises were performed first than when they were performed last in a sequence (Bellezza et al 2009;Farinatti et al 2009;Gentil et al 2007;Miranda et al 2010;Sforzo and Touey 1996;Simão et al 2005Simão et al , 2007Spreuwenberg et al 2006).…”
Section: Introductionmentioning
confidence: 84%
“…This exercise--order recommendation has been supported by studies that found greater strength gains (Dias et al 2010;Simão et al 2010;Spineti et al 2010) and hypertrophy Spineti et al 2010) in muscles that were trained at the beginning, rather than at the end, of a session during a long--term training program. Furthermore, studies examining the effect of exercise order (i.e., either large or small muscle--group exercises performed first in a training session) on repetition performance demonstrated significantly greater total repetitions (across all sets) for the same exercise when large muscle--group exercises were performed first than when they were performed last in a sequence (Bellezza et al 2009;Farinatti et al 2009;Gentil et al 2007;Miranda et al 2010;Sforzo and Touey 1996;Simão et al 2005Simão et al , 2007Spreuwenberg et al 2006).…”
Section: Introductionmentioning
confidence: 84%
“…Our results indicate that the exercises which ended the training session (BP ad LPD), were performed under previous fatigue promoted by the accessory muscles already recruited during the BC and TE performance, for being in the end of the sequence 16,24,25 , and consequently thy were less sensitive to the maximum strength increment, which indicates that the B and LPD, besides presenting lower strength increment, have not been influenced by the periodization model adopted either. Thus, higher efficiency of OP is observed in the evolution of maximum dynamic strength in the initial phase of the training for the exercises which started the session and in the muscle hypertrophy of the EE and EF; however, the same results have not been found concerning the MVIC increase.…”
Section: Discussionmentioning
confidence: 69%
“…A possible explanation for these divergences of results may be aassociated with the size of the muscular groups involved in each exercise 24 . Previous studies have demonstrated that the exercise order may influence on the development of maximum strength 16,24,25 . Additionally, our results indicate that the RT periodization model does not equally influence on all the exercises in a sequence, since the exercises which start the training session may be boosted by the manipulation of the variables referring to intensity and volume.…”
Section: Discussionmentioning
confidence: 99%
“…Em programas de musculação onde o principal objetivo é a hipertrofia/força máxima, um elevado volume associado à alta intensidade devem ser realizados para cada grupamento muscular 6,[13][14][15] , portanto, sessões direcionadas para grupos musculares sinérgicos (rotinas divididas) dentro na semana (microciclo) são sugeridas 2,[6][7][8][12][13][14]16,17 . Dentre tais estratégias de ordem de exercícios, duas são as mais utilizadas na musculação, a pré-exaustão que consiste na realização de um exercício isolado seguido por um multiarticular e o tradicional, onde se realiza a ordem inversa 5,11,[16][17][18][19] .…”
Section: Introductionunclassified